Accounting for Environmental Effects during Monitoring of the Dowling Hall Footbridge. - Moaveni, Babak.; Behmanesh, Iman. (Tufts University. Tisch Library., 2017)
This document provides an overview of three different studies to investigate the effects of ambient temperature on dynamic properties of the Dowling Hall Footbridge and how to account for these effects in structural identification. In the first study, different static (polynomial) and dynamic (autoregressive) models were proposed to represent the relationship between the identified natural frequencies and measured temperatures. In the second study, effects of changing ambient temperatures on finite element model updating of the footbridge were investigated using the proposed models from the first study. Finally, a Hierarchical Bayesian model updating framework was proposed in the third study to account for the effects of ambient temperature and excitation amplitude.